The theme of muhajirlik in Tatar prose - Aidar Ju. Khabutdinov, Marat F. Safin, Milyausha М. Khabutdinova, (Opción, 2019)
The article discusses the reception of the muhajirun as a phenomenon in the Tatar literature of the XX century. The methodological basis of the research is based on theoretical works on literary studies and history devoted to emigration. As a result, Tatar writers try to convince readers that each of us in his turn is destined to hear the call of blood and to feel the blood connection with his native land. In conclusion, most of the works affirm the absolute value of the native land in human life and the need to return home.